Clearance of systemic hematologic tumors by venetoclax (Abt-199) and navitoclax - Ackler, Scott (Pharmacol Res Perspect, 2015)
The Bcl-2 family inhibitors venetoclax and navitoclax demonstrated potent antitumor activity in chronic lymphocytic leukemia patients, notably in reducing marrow load and adenopathy. Subsequent trials with venetoclax have been initiated in non-Hodgkin's lymphoma and multiple myeloma patients. Traditional preclinical models fall short either in faithfully recapitulating disease progression within such compartments or in allowing the direct longitudinal analysis of systemic disease. We show that intravenous inoculation of engineered RS4;11 (acute lymphoblastic leukemia) and Granta 519 (mantle cell lymphoma) bioluminescent reporter cell lines result in tumor engraftment of bone marrow, with additional invasion of the central nervous system in the case of Granta 519. Importantly, apoptosis induction and response of these systemically engrafted tumors to Bcl-2 family inhibitors alone or in combination with standard-of-care agents could be monitored longitudinally with optical imaging, and was more accurately reflective of the observed clinical response.